Comparing the self-assembly processes of two redox-active exTTF-based regioisomer ligands. (11th November 2021) - Dekhtiarenko, Maksym; Allain, Magali; Carré, Vincent; Aubriet, Frédéric; Voitenko, Zoia; Sallé, Marc; Goeb, Sébastien
Abstract : A new exTTF-based ligand was synthesized and its coordination-driven self-assembly behavior with a square planar palladium complex was compared with a previously described regioisomer. Abstract : The synthesis of a new tetratopic extended-TTF (exTTF; 9, 10-di(1, 3-dithiol-2-ylidene)-9, 10-dihydroanthracene) ligand, bearing four pyridyl coordinating functions on the dihydroanthracenyl platform rather than on the 1, 3-dithiol rings (previously described regioisomer), was reported. The self-assembly behaviors of both electroactive regioisomers were compared. While a M4 L2 container was obtained with the previous one when reacted with the square planar Pd(dppf)OTf2 complex, the new ligand, when reacted under the same conditions, affords a M6 L3 hexagonal structure that is composed of nine electro-active subunits that can be reversibly oxidized.